Error cascades in observational learning: An experiment on the Chinos game - Francesco Feri; Miguel A. Meléndez-Jiménez; Giovanni Ponti; Fernando Vega Redondo (University of Innsbruck, Department of Public Finance, 2008)
The paper reports an experimental study based on a variant of the popular Chinos game, which is used as a simple but paradigmatic instance of observational learning. There are three players, arranged in sequence, each of whom wins a fixed price if she manages to guess the total number of coins lying in everybody's hands. Our evidence shows that, despite the remarkable frequency of equilibrium outcomes, deviations from optimal play are also significant. And when such deviations occur, we find that, for any given player position, the probability of a mistake is increasing in the probability of a mistake of her predecessors. This is what we call an error cascade, which we which we measure by way of two alternative models.
Keywords: C92; D8; 330; positional learning; error cascades; Spieltheorie; Lernprozess; Unvollkommene Information; Statistischer Fehler; Theorie